Oral health status of students with visual or hearing impairments in Northeast China - Jian Li; Kaiqiang Zhang; Chang Cha; Zhenfu Lu; Lu Liu (BMC, 2023)
Abstract Background Visual or hearing impairments in students seriously affect their quality of life. The aim of this study was to identify oral hygiene status and its influencing factors on visual or hearing impairments in students in Northeast China. Methods This study was conducted in May 2022. A total of 118 visually impaired students and 56 hearing impaired students from Northeast China were included in this study via census. Oral examinations and questionnaire-based surveys of students and their teachers were conducted. The oral examinations included caries experience, prevalence of gingival bleeding and dental calculus. The questionnaires included three parts: Social demographics (residence, sex and race) and parents' educational level; Oral hygiene habits and medical treatment behaviors; Knowledge and attitudes towards oral health care. This questionnaire was selected from the Fourth China National Oral Health Survey and the reliability and validity of the questionnaire were previously tested. T tests, one-way ANOVA, χ 2 tests and multivariate logistic analyses were conducted to evaluate the differences and dependent variables of dental caries. Results The prevalence of dental caries in visually impaired and hearing impaired students were 66.10% and 66.07%. The mean number of DMFT, prevalence of gingival bleeding and dental calculus in visually impaired students were 2.71 ± 3.06, 52.08% and 59.38%, respectively. The mean number of DMFT, prevalence of gingival bleeding and dental calculus in hearing impaired students were 2.57 ± 2.83, 17.86% and 42.86%, respectively. The results of the multivariate logistic analysis showed that fluoride use and parents' educational background had an impact on the caries experience of visually impaired students. The daily toothbrushing frequency and parents' educational background had an impact on the caries experience of hearing impaired students. Conclusions The oral health situation of students with visual or hearing impairments remains severe. It is still necessary to promote oral and general health in this population.